Construction of T7-Like Expression System in Pseudomonas putida KT2440 to Enhance the Heterologous Expression Level - Liang, Tianxin; Sun, Jun; Ju, Shuyun; Su, Shenyi; Yang, Lirong; Wu, Jianping (Frontiers in Chemistry, 2021)
Pseudomonas putida KT2440 has become an attractive chassis for heterologous expression with the development of effective genetic manipulation tools. Improving the level of transcriptional regulation is particularly important for extending the potential of P. putida KT2440 in heterologous expression. Although many strategies have been applied to enhance the heterologous expression level in P. putida KT2440, it was still at a relatively low level. Herein we constructed a T7-like expression system in P. putida KT2440, mimicking pET expression system in Escherichia coli, which consisted of T7-like RNA polymerase (MmP1) integrated strain and the corresponding expression vector for the heterologous expression enhancement. With the optimization of the insertion site and the copy number of RNA polymerase (RNAP), the relative fluorescence intensity (RFI) of the super-folder green fluorescent protein (sfGFP) were improved by 1.4-fold in MmP1 RNAP integrated strain. The induction point and IPTG concentration were also optimized. This strategy was extended to the gene-reduced strain EM42 and the expression of sfGFP was improved by 2.1-fold. The optimal RNAP integration site was also used for introducing T7 RNAP in P. putida KT2440 and the expression level was enhanced as well, indicating the generality of integration site for T7 expression system. Compared to other inducible expression systems in KT2440, the heterologous expression level of Mmp1 system and T7 system were more than 2.5 times higher. Furthermore, the 3.6-fold enhanced expression level of a difficult-to-express nicotinate dehydrogenase from Comamonas testosteroni JA1 verified the efficiency of the T7-like expression system in P. putida KT2440. Taken together, we constructed and optimized the T7-like and T7 expression system in P. putida, thus providing a set of applicable chassis and corresponding plasmids to improve recombinant expression level, expecting to be used for difficult-to-express proteins.